Gender Violence in Prison & Hyper-masculinities in the 'Hood: Cycles of Destructive Masculinity - SpearIt (Washington University Journal of Law & Policy, 2011)
Part I concludes the introduction to the essay’s thesis by discussing the gender norms in society that rely heavily on the debasement of women. Part II, Documenting Destructive Masculinity, surveys documentary sources, from classic prison biographies to audio-visual works, to examine gender violence in prison. As opposed to some studies based on “random” samples for interview or survey, this Article approaches the problem by focusing on inmates who claim first-hand knowledge of victimization. From these documentary sources the possibilities and permutations of gender violence emerge, including among inmates, guard-on-inmate, and inmate-on-guard. Part III, Structural Impediments, examines legal, political, and administrative factors which help foster the destructive behaviors described in the previous part. It tells of shortcomings in prison policies and procedures that contribute systemically to victimization. There is considerable debate on the prevalence of sexual violence in prison, but to the extent it exists, structural failures in prisons and in the law contribute to the problem as well. In Part IV, Ghetto Girls and Boys Beware, the Article shifts focus to outside of prison, to the states in which tens of thousands of inmates are released each year. It theorizes how cycles of destructive masculinity disproportionately affect marginal communities. Finally, Part V, Prospects for Damage Control, proposes a set of ideas to combat gender violence in both prisons and the outside. Looking to the future, this part considers legal and community interventions which may help mitigate the social costs of gender violence; prisoners, prison staff, and scholars all have sensible ideas about what can help assuage the problem. The question is whether anyone is listening.
Keywords: Masculinity; Prison violence; Rape; Prison Rape Elimination Act of 2003; United States